Chronic ulcerative Cutaneous Vasculitis of the legs Clinical and histopathological study - Hamed, Thamir A.; Al-Hamamy, Hayder R.; Salman, Husam A.; Al-Waiz, Mukram M (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Cutaneous small vessel vasculitis characterized by necrosis and inflammation of upper dermal blood vessels. It presents with ulcers and systemic manifestations after extensive acute onset. Many patients have a form of cutaneous vasculitis that presents with chronic painful ulcerations & purpuras involving the ankles without systemic manifestations, with some similarity in clinical presentation to livedoid vasculopathy.Patients and Methods: Thirteen patients were seen in the Department of Dermatology and Venereology, Baghdad Teaching Hospital, for a period extending from January 2004 to March 2005. They were evaluated clinically, histopathologically and other laboratory studies. In addition, evaluation of the clinical response to prednisolone 0.5mg/kg/day and azathioprine150mg/day was done.Results: Thirteen patients were included in this study; eight females and five males, with male to female ratio of 1:1.6. Their ages ranged between 26-66 years with a mean ±SD of 42 ± 13.8 years. The duration of the disease ranged from 0.5 – 18 years with a mean ±SD of 38 ± 59.2 months.The clinical examination revealed multiple oval punched out ulcers, with an indurated base, and surrounded by a zone of erythema; affecting mainly the ankles and dorsa of feet. Histopathological evaluation showed upper dermal vessels' wall necrosis, fibrinoid deposition, obliteration of the lumen, extravasation of red blood cells, endothelial cells swelling with perivascular and vascular wall infiltration mainly by mononuclear cells.The treatment was started with prednisolone & azathioprine. The ulcers healed completely with residual hyperpigmentation - hypopigmentation, atrophy and scars within 10-15 weeks Conclusions: Chronic ulcerative cutaneous vasculitis is often a neglected and misdiagnosed variant of vasulitis. Histologically it has vascuiltic features, and clinically looks like livedoid vasculopathy.